Kinetic and thermodynamic studies on biosorption of Ni (II) and Cd (II) by chemically modified lemon peel - Villén-Guzmán, María Dolores; Arhoun, Brahim; Cerrillo-González, María del Mar; Paz-García, Juan Manuel; Rodríguez-Maroto, José Miguel (My University, 2020)
The valorization of agricultural wastes as biosorbent represents a promising circular economy strategy: a waste is applied for the treatment of wastewater containing contaminants. This work is focused on the removal of Ni and Cd encountered in aquatic systems, such as industrial effluents from battery manufacturing, electroplating and mine drainage.
Keywords: Plantas depuradoras de agua; Residuos agrícolas; Níquel; Cadmio